Floating microplastic inventories in the southern Beaufort Sea, Arctic Ocean - Takahito Ikenoue; Ryota Nakajima; Pravakar Mishra; Eswara Venkatesaperumal Ramasamy; Amane Fujiwara; Shigeto Nishino; Akihiko Murata; Eiji Watanabe; Motoyo Itoh (Frontiers in Marine Science, 2023)
The microplastics inflow into the Arctic Ocean may increase environmental stress on the Arctic marine ecosystem on the Pacific side, where sea ice has been significantly reduced because of global warming. However, quantitative data on microplastics are very limited in the Beaufort Sea, which is covered by sea ice for most of the year, even in summer. We therefore observed microplastic concentrations over a wide area of the southern Beaufort Sea using a neuston net from 30 August to 10 September 2022 to estimate the total number (particle inventory) and mass (mass inventory) of microplastics in the entire water column. The particle inventory during the sampling period ranged from 937 to 28,081 pieces km−2 (mean ± standard deviation, 7570 ± 7600 pieces km−2). The mass inventory of microplastics ranged from 22 to 664 g km−2 (179 ± 180 g km−2). Relatively high microplastic inventories (>6500 pieces km−2) were observed off Utqiaġvik and the mouth of the Mackenzie River, suggesting that some microplastics originate not only in the Pacific but also in the Arctic. These values indicate that waters in the southern Beaufort Sea is contaminated with microplastics to the same order of magnitude as the Chukchi Sea.